Impact of knowledge management practices on firm performance: Testing the mediation role of innovation in the manufacturing sector of Pakistan - Muhammad Saqib Nawaz; Masood ul Hassan; Sadia Shaukat (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
With the emergence of intellectual capital and knowledge management as new disciplines, organizational authors and practitioners added these constructs as possible antecedents of the innovation. In consistent with this stream of research, this study aims to find the impact of three knowledge management practices i.e. knowledge acquisition, knowledge dissemination and responsiveness to knowledge on innovation and firm performance. For this purpose, data was collected from 407 manufacturing organizations listed in Karachi Stock Exchange, representing mainly textile, FMCG, cement, petroleum, fertilizers, pesticides, chemicals, electronics, pharmaceuticals and other sectors. SPSS has been used for data analysis. Factor analysis and Cronbach's alpha confirmed the validity and reliability of the measurement scales. Similarly, correlation and regression analysis were applied to find out the relationship among independent variables (Knowledge management practices), mediating variable (innovation) and dependent variable (firm performance). The findings show positive and significant relationship among all the study variables. Specifically, innovation partially mediates the relationship between knowledge management practices and firm performance. Theoretical & managerial implications along with limitations and recommendations for future research have also been discussed in the paper.
Keywords: 330; manufacturing sector; Karachi Stock Exchange; innovation; textile